The Positive Allosteric Modulator of Alpha-2/3-Containing γ-Aminobutyric Acid Type A Receptors, KRM-II-81, Is Active in Pharmacoresistant Models of Epilepsy and in Human Epileptic Tissue. (1st September 2019) - Smith, Jodi L; Ping, Xingie; Jin, Xiaoming; Golani, Lalit K; Li, Guanguan; Rashid, Farjana; Jahan, Rajwana; Cook, James M; Witkin, Jeffrey M
Abstract: INTRODUCTION: Epilepsy patients continue to suffer from the lack of efficacious medications. Recent attention has been directed toward the potential advantages of developing positive allosteric modulators of alpha-2/3-containing γ-aminobutyric acid type A (GABAA) receptors as antiepileptic drugs. A proof of principle has been reported with one such molecule in patients with photosensitive epilepsy. KRM-II-81 (5- (8-ethynyl-6- (pyridin-2-yl)-4H-benzo[f]imidazole[1, 5-alpha][1, 4]diazepin-3-yl)oxazole) is an orally-bioavailable compound recently designed for selectivity at alpha-2/3-containing GABAA receptors over the alpha-1-subtype involved in motor-impairing effects. KRM-II-81 has recently been reported to dampen seizure activity in rodents induced by acute and chronic seizure provocation. KRM-II-81 was often more efficacious than diazepam as an anticonvulsant while producing less motor impairment than diazepam. The reduced motor impact of KRM-II-81 is hypothesized to enable higher central target exposure and hence increased efficacy. METHODS: The effects of KRM-II-81 were investigated in a mouse mesial temporal lobe model and a rat lamotrigine-resistant kindling model. We also explored the antiepileptic electrophysiological effects of KRM-II-81 in cortical slices from epileptic pediatric patients to help guide the development of novel compounds that might be valuable against antiepileptic drug-resistant epilepsies. RESULTS: Mice with kainate-induced mesial temporal lobe seizures exhibited spontaneous recurrent hippocampal paroxysmal discharges (16.8 +/–2.5). KRM-II-81 significantly reduced the discharge frequency to 5.5 +/–1.4 after oral dosing at 15 mg/kg. KRM-II-81 also decreased convulsions in rats undergoing amygdala kindling in the presence of lamotrigine. In slices of epileptic cortex, KRM-II-81 produced a concentration-dependent dampening of network activity engendered by the GABAA receptor antagonist picrotoxin or the K + -channel modulator 4-aminopyridine. CONCLUSION: This study provides increased levels of confidence regarding the unique anticonvulsant profile of KRM-II-81 and its potential as an improved antiepileptic drug. The data also help to solidify the veracity of alpha-2/3-containing GABAA receptors as a novel molecular target for antiepileptic drugs.